The SAGE handbook of social work research - Shaw, Ian, 1945- (London : SAGE, 2010)
Ranging over local and international issues and exploring questions of theory and practice, this diverse study provides a comprehensive account of the state of the art of social work research. It invites us to understand the historical roots of the unresolvable tensions within the purposes and methods of social work research.
Includes bibliographical references (p. 477-547) and index.
Keywords: Social service -- Research